DIFFERENTIATION IN THE ATTITUDES OF SECONDARY SCHOOL FEMALE STUDENTS TOWARDS A HEALTHY LIFESTYLE - Dževad Džibrić (Sport Scientific And Practical Aspects, 2025)
A healthy lifestyle is important not only for the individual but also for society as a whole. A healthy person can actively and efficiently perform various tasks and thus become a useful member of society. This research aimed to determine the differences in attitudes towards a healthy lifestyle between students in different grades of high school. The population from which the sample of 256 respondents was taken was defined as the population of students of I, II, III, and IV grade of high schools from Tuzla, aged 15-18 years ± 6 months. A survey questionnaire was used to assess attitudes about a healthy lifestyle, which consisted of 25 items especially evaluated on a 5-point scale. To determine the differences in attitudes towards a healthy lifestyle between students of different grades, the Kruskal Wallis test was applied. The obtained results showed that there are statistically significant differences between the treated groups in 11 particles (6 particles that determine the cognitive component of attitude, ie in 3 particles that determine the affective and 2 particles that determine the behavioral component of attitude. first and fourth grade. A healthy lifestyle is not something we are given at birth but must be learned and patiently developed throughout life. Therefore, the role of kinesiologists in high schools is multiple and aims to prepare students for active use of free time by promoting regular physical exercise and a healthy lifestyle.